Persepsi Masyarakat terhadap Kegiatan Olahraga yang ada di Lingkungan Kampus 3 Universitas Negeri Gorontalo - Mahmud, Iskandar; Haryani, Meri; Alamri, Sakina; Palakum, Agrilan; Kadir Saleh, Abd (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This study aims to determine public perceptions of sports activities carried out on campus. The perceptions in question include the views of students, lecturers, campus staff, and the surrounding community on the benefits, impacts, and implementation of sports activities. The method used in this study was a descriptive survey ‘with an instrument in the form of a questionnaire distributed to respondents from various backgrounds. The results of the study showed that the majority of respondents had a positive perception of campus sports activities, especially in terms of health, character building, and increasing social interaction. However, several critical notes were also found regarding uneven facilities and noise disturbances felt by some of the surrounding community. . These findings are expected to be input for the campus to improve the quality and management of sports activities to be more inclusive and have a positive impact overall